Exploring the Morphometry of Infraorbital and Mental Foramina: Insights from a Local Anatomical Study - Ammara Rasheed; Mirani, Ponum; Hina, Mohtasham; Rasheed, Nida; Tasleem, Maria (Journal of Rawalpindi Medical College, 2025)
Objective: The study aims to determine the dimensions of the IOF and MF, their distances from clinically significant anatomical landmarks, and their potential variations in a local population. Methods: The study was conducted in the Anatomy Department of Nishtar Medical University, Multan, from June 2024 to November 2024. A descriptive study was performed on 132 dry adult human skulls. The transverse and vertical diameters of the IOF and MF, along with their respective distances to the anterior nasal spine (for IOF) and symphysis menti (for MF), were measured using digital Vernier callipers. Measurements were taken twice by the authors to minimise errors. Data analysis was performed using SPSS version 20.0, with results expressed as mean ± standard deviation. Results: All skulls exhibited a single IOF and MF bilaterally. The mean transverse diameter of the IOF was 2.858 ± 0.633 mm (right) and 3.112 ± 0.823 mm (left), while its vertical diameter was 4.199 ± 0.732 mm (right) and 4.229 ± 0.887 mm (left). The mean IOF-to-anterior nasal spine distances were 32.22 ± 3.73 mm (right) and 31.48 ± 3.53 mm (left). For the MF, the mean transverse diameter was 2.81 ± 0.65 mm (right) and 2.92 ± 0.71 mm (left), while the vertical diameter was 2.96 ± 0.69 mm (right) and 3.01 ± 0.72 mm (left). The distance of MF from the symphysis menti was 25.43 ± 2.34 mm (right) and 25.16 ± 2.29 mm (left). These findings provide valuable anatomical data for clinicians performing surgical and anaesthetic interventions in the midface and lower face regions. Conclusion: The findings of this study contribute to a growing body of evidence on IOF and MF morphology, emphasizing population-specific variations. This localised data is essential for clinicians performing surgical and anaesthetic procedures in the midface and lower face, ensuring safer and more effective interventions. Keywords: Infraorbital foramen, mental foramen, local population, regional anaesthesia